On the Potential Function of Type II Arabinogalactan O-Glycosylation in Regulating the Fate of Plant Secretory Proteins - Seifert, Georg J. (Frontiers in Plant Science, 2020)
In a plant-specific mode of protein glycosylation, various sugars and glycans are attached to hydroxyproline giving rise to a variety of diverse O-glycoproteins. The sub-family of arabinogalactan proteins is implicated in a multitude of biological functions, however, the mechanistic role of O-glycosylation on AGPs by type II arabinogalactans is largely elusive. Some models suggest roles of the O-glycans such as in ligand-receptor interactions and as localized calcium ion store. Structurally different but possibly analogous types of protein O-glycosylation exist in animal and yeast models and roles for O-glycans were suggested in determining the fate of O-glycoproteins by affecting intracellular sorting or proteolytic activation and degradation. At present, only few examples exist that describe how the fate of artificial and endogenous arabinogalactan proteins is affected by O-glycosylation with type II arabinogalactans. In addition to other roles, these glycans might act as a molecular determinant for cellular localization and protein lifetime of many endogenous proteins.